Installing and Implementing a Computer-based Patient Record System in Sub-Saharan Africa: The Mosoriot Medical Record System - Rotich, Joseph K. (American Medical Informatics Association, 2003)
The authors implemented an electronic medical record system in a rural Kenyan health center. Visit data are recorded on a paper encounter form, eliminating duplicate documentation in multiple clinic logbooks. Data are entered into an MS-Access database supported by redundant power systems. The system was initiated in February 2001, and 10,000 visit records were entered for 6,190 patients in six months. The authors present a summary of the clinics visited, diagnoses made, drugs prescribed, and tests performed. After system implementation, patient visits were 22% shorter. They spent 58% less time with providers (p < 0.001) and 38% less time waiting (p = 0.06). Clinic personnel spent 50% less time interacting with patients, two thirds less time interacting with each other, and more time in personal activities. This simple electronic medical record system has bridged the “digital divide.” Financial and technical sustainability by Kenyans will be key to its future use and development.